Diversity and conservation of mammals in indigenous territories of southern Mexico: proposal for an “Archipelago Reserve” - Briones-Salas,Miguel; Galindo-Aguilar,Rosa E.; González,Graciela E.; Luna-Krauletz,María Delfina (PeerJ, 2023)
Southern Mexico’s tropical forests are home to the country’s highest richness of mammal species; La Chinantla region is situated within this area, its name from the indigenous group residing in the area and holding territorial ownership, namely the Chinantecos. In La Chinantla, there are no Protected Areas; instead, there are Areas Destined Voluntarily for Conservation (ADVC) and “Voluntary Conservation Areas” (VCA), that are managed by local inhabitants through social consensus. These ADVC may function as an archipelago reserve, which represents regional diversity, including the social context, through complementarity. To verify its biodiversity, we analyzed the richness, composition, distribution, and conservation of wild mammals in the region. Records were obtained from four sources—primary data collection, databases, scientific literature, and community monitoring—and were organized into four zones based on altitudinal and vegetation gradients. We compared the diversity between zones for three categories of mammals: small (<100 gr.), bats, and medium and large (>100 gr.). 134 species were identified comprising 11 orders, 26 families and 86 genera. The zone with highest elevation presented the greatest species richness for the assemblage of mammals and terrestrial mammals, while the zone with the lowest elevation had the highest richness of bats. For each mammal category, the zone with the most species also registered the highest number of exclusive species. For the assemblage of mammals and for medium and large mammals, the similarity index was highest between the two intermediate zones, while for small mammals and bats, the greatest similarity occurred between the areas of higher altitude. The study region was found to have the second highest richness of mammals in Mexico. Finally, we suggest that the conservation proposals by indigenous people could function as a set of “islands” that promote the conservation of biodiversity, possibly as an Archipelago Reserve.
Keywords: Áreas destinadas voluntariamente a la conservación; Tropical rainforest; Cloud forest; Chinantla; Bats; Sierra Madre de Oaxaca